2020
DOI: 10.18483/ijsci.2350
|View full text |Cite
|
Sign up to set email alerts
|

Local Uses and Parasitism of Loranthaceae in Sudano-Sahelian Zone of Cameroon: Case of Diamare Plain in Far North Region

Abstract: The Loranthaceae, commonly referred to "mistletoe from Africa" are used by communities of Cameroon for their numerous therapeutic virtues. The study examined the local various uses of Loranthaceae species in Diamare plain of Cameroon. Participatory rural appraisal method was used with 130 persons, namely traditional healers, breeders, farmers and foresters in order to identify the local uses of Loranthaceae species. We used itinerary botanical survey method in thirty-two (32) villages for the inventory of Lora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…This will reduce a large part of the mistletoe density on V. paradoxa and P. biglobosa given these mistletoes were the most abundant in the study area. The preponderance of medicinal uses of mistletoes revealed in this work is well recognized worldwide [ 20 , 24 , 48 , 49 ] and explained by the active compounds they contained [ 50 , 51 ]. Thus, we recommend the use of mistletoes in the production of improved traditional medicines to significantly reduce their density and then contribute to the improvement of human health [ 30 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This will reduce a large part of the mistletoe density on V. paradoxa and P. biglobosa given these mistletoes were the most abundant in the study area. The preponderance of medicinal uses of mistletoes revealed in this work is well recognized worldwide [ 20 , 24 , 48 , 49 ] and explained by the active compounds they contained [ 50 , 51 ]. Thus, we recommend the use of mistletoes in the production of improved traditional medicines to significantly reduce their density and then contribute to the improvement of human health [ 30 ].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, several mistletoe control methods were implemented through mechanical, chemical, and biological approaches [ [14] , [15] , [16] ]. However, mistletoe control is reported to be poorly adopted given its complexity and especially the ecological and socio-economic values of these plants [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Indeed, Griebel et al [ 22 ] reported mistletoes ecologically promote wildlife habitat, biodiversity, and nutrient cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Aujourd'hui, au-delà de leurs utilisations dans le traitement de différentes affections, l'exploitation durable des Loranthaceae est d'un grand intérêt pour les communautés locales à cause de ses retombées économiques par la commercialisation des bottes des espèces récoltées. Malgré l'importance des Loranthaceae en pharmacopée, à l'état actuel des connaissances, très peu d'études ont été réalisées sur les Loranthaceae et l'influence des collines sur leur distribution dans la Région de l'Extrême-Nord, Cameroun (Souare et al, 2020). Cette étude vise donc à évaluer la diversité spécifique des Loranthaceae parasites des plantes ligneuses des Monts Mandara dans la Région de l'Extrême-Nord du Cameroun, déterminer l'influence des collines sur leur distribution et relever leur importance socio-économique.…”
Section: Introductionunclassified